Model Pembiayaan Infrastruktur Melalui Perusahaan Dana Pensiun Dengan Instrumen Sukuk Yang Diterbitkan Oleh Perusahaan BUMN - Rahmayati Rahmayati (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2017)
This study aims to offer a model in terms of infrastructure development in Indonesia through the issuance of sukuk which is adjusted based on the purpose of use and the type of infrastructure, namely Musyarakah Muqtanaqishah (MMQ), Ijarah, Mudharabah, Murabahah, and Isthisna by state-owned companies then offer the Sukuk to the company pension fund. The methodology in this research uses a system thinking approach with secondary data collection techniques obtained from supporting literature. The result of this research is that the NBFI industry in Indonesia is very important role for the development of infrastructure with the media of pension fund where the instrument is the Sukuk by using musyarakah and Musyarakah Muqtanaqishah (MMQ).